Analysis of chemical compounds of agarwood oil from different species by gas chromatography mass spectrometry (GCMS) - Hashim, Yumi Zuhanis Has-Yun; Ismail, N.I.; Abbas, P. (IIUM Press, 2014)
Agarwood oil is a highly prized type of oil due to its unique aroma. The oil is extracted from the fragrant resin found in the agarwood tree (trunk). The unique aroma and quality of agarwood resin and oil are contributed by the presence of certain chemical compounds. In this work, analysis and comparison of the chemical compounds of agarwood oil from A. malaccensis, A. sub-integra and a mixture of both were conducted. The essential oils were diluted in hexane (5%) prior to gas chromatography mass spectrometry (GCMS) analysis performed using Agilent GCMS 7890A coupled with MSD quadrupole detector 5975 C. Separation of analytes by gas chromatography was carried out using a Hewlett Packard HP-5MS silica capillary column (30 m X 0.25 mm X 0.25 mm). A total of 107 compounds were identified from the three samples of agarwood oils. Fifty-five (55) components were identified in A. malaccensis sample which contributes to the largest portion of the total compounds. About 20% of the compounds identified were aromatic and sesquiterpenes which have been revealed to be the main active compounds of agarwood oils which also give the aroma and pleasant odour of agarwood. Different compositions or profile of chemical components were found in agarwood oils from the two different species. Two compounds were commonly identified in all three samples namely 3-phenyl-2-butanone and alpha-cubebene. Further studies are needed to refine the results which later can be used to assist detection and authentication of agarwood as well as its scientific-based grading.